2013
DOI: 10.1371/journal.pone.0055036
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to Experimental Jet-Lag in R6/2 Mice despite Circadian Dysrhythmia

Abstract: The R6/2 transgenic mouse model of Huntington’s disease (HD) shows a disintegration of circadian rhythms that can be delayed by pharmacological and non-pharmacological means. Since the molecular machinery underlying the circadian clocks is intact, albeit progressively dysfunctional, we wondered if light phase shifts could modulate the deterioration in daily rhythms in R6/2 mice. Mice were subjected to four x 4 hour advances in light onset. R6/2 mice adapted to phase advances, although angles of entrainment inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 32 publications
2
12
0
Order By: Relevance
“…As seen previously under DD, with age R6/2 mice exhibited a progressively shorter period length than was seen in WT mice (Wood et al, 2013;Ouk et al, 2017). In mice under DD at 12-13 weeks of age, there was a main effect of genotype on period length (F (1,32) ϭ 16.2; p ϭ 3E-4 w ), amplitude of rhythms (F (1,32) ϭ 14.41; p ϭ 0,0006 x ), and activity counts (F (1,32) ϭ 21.43; p ϭ 6E-5 y ), with all these parameters significantly decreased in R6/2 mice compared with WT mice (Fig.…”
Section: Entrainment To Constant Light and Constant Darkness In R6/2 supporting
confidence: 80%
See 4 more Smart Citations
“…As seen previously under DD, with age R6/2 mice exhibited a progressively shorter period length than was seen in WT mice (Wood et al, 2013;Ouk et al, 2017). In mice under DD at 12-13 weeks of age, there was a main effect of genotype on period length (F (1,32) ϭ 16.2; p ϭ 3E-4 w ), amplitude of rhythms (F (1,32) ϭ 14.41; p ϭ 0,0006 x ), and activity counts (F (1,32) ϭ 21.43; p ϭ 6E-5 y ), with all these parameters significantly decreased in R6/2 mice compared with WT mice (Fig.…”
Section: Entrainment To Constant Light and Constant Darkness In R6/2 supporting
confidence: 80%
“…While our Per1 light-induced expression data support previous findings that the molecular machinery of the SCN is intact, they also indicate that retinal dysfunction is unlikely to be the sole cause of dysrhythmia in R6/2 mice. In support of this suggestion, previous studies have shown that R6/2 mice respond to bright light (Cuesta et al, 2014), jet lag (Wood et al, 2013), and photoperiod length variation (Ouk et al, 2017). This raises the possi-bility that the involvement of downstream areas of the brain innervated by the SCN causes the disruption of the behavioral response to the phase-delaying light pulse.…”
Section: Discussionmentioning
confidence: 71%
See 3 more Smart Citations